ANALISIS KETERAMPILAN PREDIKSI DAN MENGKOMUNIKASIKAN MELALUI PENERAPA MODEL PROBLEM SOLVING - Siti Aisah; Ila Rosilawati; Tasviri Efkar (Universitas Lampung, 2013)
This research aims to describe the prediction and communication skill on acid-base material through application problem solving model to the cognitive students group with high, medium, and low category. This research used pre-experiment method with One Shot Case Study Design. The Subject in this research was class XI_science4 students of MAN 1 Bandar Lampungt academic year 2012-2013. The data analysis used descriptive analysis. The result showed: (1)Prediction skill, almost half students have excellent criteria and most students have good in high category; almost half students have good criteria, the rest of students have excellent, average, and poor in medium category; most students have good criteria, the rest of students have excellent, average, and poor in low category. (2)communication skill, all students have excellent criteria in high category; almost all students have excellent criteria, the rest of students have good in medium and low category. The high category have predictin and communication skill more high than medium and low category. Kata Kunci : problem solving, prediksi, komunikasi, kelompok tinggi, kelompok sedang, kelompok rendah